The importance of regional variation in the analysis of urbanization-agriculture interactions - Bryant, C.; Greaves, S. (Cahiers de géographie du Québec)

(untitled) (Département de géographie de l'Université Laval, 1978)
Research into agriculture in metropolitan regions has concentrated on urban-induced agricultural land use changes. Other processes of change and factors related to variations in the regional environment have been neglected. Some recent research is reported here which points to the importance of the regional environment at a variety of scale levels. First, a typology of regions based on Census Metropolitan Areas in Canada is developed. Some groups of regions experienced significant agricultural changes quite unrelated to metropolitan development pressures. Regional differences in the agricultural environment are suggested as partial explanations. Second, for the Montréal region, a series of agricultural variables (1961 to 1971) are analysed using factor analysis. Results are interpreted in the light of a) urbanisation forces and b) internal variation in the regional environment. Finally, for a township near Toronto, an investigation is made of the distribution of severances. Once more, relationships appear with certain physical characteristics. The paper concludes that agricultural change is not uniform either between regions or within regions, and that part of the variation is related to differences in the "regional" environment and part to metropolitan forces.